PEMODELAN PROFIL MUKA AIR BANJIR RENCANA BANGUNAN CULVERT PADA SUNGAI KRUENG JAMBO BALEE - Amir Fauzi; Khairul Iqbal; Purwandy Hasibuan (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2023)
Krueng Jambo Balee River, which is a tributary in Krueng Jambo Aye river basin, flows through the Pertagas pipeline installation (RoW, right of way), at segment of Sta. 8+500 to Sta. 8+600. Flooding that occurred at RoW Jambo Balee was caused by the draining capacity of the existing culverts which were unsufficient to flow discharge from the upstream river, thus inundating the surrounding area, and overtopping occurred on the RoW. This condition is a serious problem for the security of vital objects for the oil and gas industry, as well as disrupting the activities of the surrounding people who use the RoW as a village road. The analysis in this study aims to design alternative types and dimensions of flood control structures, i.e in this study is culverts. The alternatives were analyzed using HEC-RAS model. The modeling results show that the net width of the culvert needed to allow floods to pass through the 25-year return period is 8.5 meters, height of the culvert from the riverbed is 3,0 meters, and the width follows the width of the RoW, i.e. 6.0 meters. The water level profile for the magnitude of the 25-year flood gives a flood water level of 2.39 m from the river bed (elevation +36.39 m), where the inlet is not submerged. This study provides a technical plan for the design of culverts for river management, as well as flood management and control measures at the RoW Jambo Balee.